2013
DOI: 10.1016/j.ridd.2013.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with a history of specific language impairment (SLI): Strengths and difficulties in social, emotional and behavioral functioning

Abstract: HighlightsAdolescents with SLI report having more difficulties with peers.They also report having more mental health problems than do typical adolescents.Problematic peer relations is the strongest differentiator between the two groups.Poorer receptive language is related to more emotional/behavioral problems.Despite peer difficulties, most adolescents with SLI see themselves as prosocial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
138
1
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 45 publications
11
138
1
17
Order By: Relevance
“…We are aware that gender differences could have influenced the effects reported in this study, given that boys tend to show more externalizing problems than girls (Ketelaars et al, 2010;Conti-Ramsden et al 2013). However, the opposite pattern (girls experiencing more problems than boys) is usually reported for internalizing problems (Conti-Ramsden et al 2013), which was actually the most frequent type of behaviors problems reported in this sample. Besides that, all language groups comprised mainly boys (at least 70 %) and we still found a significant association between behavioral problems and the severity of language deficits.…”
Section: Discussionmentioning
confidence: 96%
“…We are aware that gender differences could have influenced the effects reported in this study, given that boys tend to show more externalizing problems than girls (Ketelaars et al, 2010;Conti-Ramsden et al 2013). However, the opposite pattern (girls experiencing more problems than boys) is usually reported for internalizing problems (Conti-Ramsden et al 2013), which was actually the most frequent type of behaviors problems reported in this sample. Besides that, all language groups comprised mainly boys (at least 70 %) and we still found a significant association between behavioral problems and the severity of language deficits.…”
Section: Discussionmentioning
confidence: 96%
“…An existing clinical concern is that the services delivered to children with SLI do not address the underlying problem of the disorder. This may result in language difficulties that persist in adulthood, which can contribute to poor quality of life [78]. If evidence suggests that the mechanism underlying both the language and motor deficits in SLI is procedural memory, then services can focus on strengthening procedural skills and possibly yield long-lasting improvements in the child's language and motor abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is accumulating evidence that children with LI are also prosocial (Conti-Ramsden, Mok, Pickles, & Durkin, 2013), and that this is a key characteristic differentiating children with LI and children with autism spectrum disorders (Charman, Ricketts, Dockrell, Lindsay, & Palikara, 2015). Children with LI who are more prosocial have more positive peer relations and better social outcomes (Mok et al, 2014).…”
mentioning
confidence: 99%